Integrative analysis of non-targeted metabolome and transcriptome reveals the mechanism of volatile formation in pepper fruit - Liu, Yuhua; Zhou, Jiahao; Yi, Cheng; Chen, Fengqingyang; Liu, Yan; Liao, Yi; Zhang, Zhuqing; Liu, Wei; Lv, Junheng (Frontiers in Genetics, 2023)
Aroma is a key inherent quality attributes of pepper fruit, yet the underlying mechanisms of aroma compound biosynthesis remain unclear. In this study, the volatile profile of the QH (cultivated Capsicum chinense) and WH (cultivated Capsicum annuum) pepper varieties were putatively identified during fruit development using gas chromatography-mass spectrometry (GC-MS). The results identified 203 volatiles in pepper, and most of the esters, terpenes, aldehydes and alcohols were significantly down-regulated with fruit ripening. The comparison of volatile components between varieties revealed that aldehydes and alcohols were highly expressed in the WH fruit, while esters and terpenes with fruity or floral aroma were generally highly accumulated in the QH fruit, providing QH with a fruity odor. Transcriptome analysis demonstrated the close relationship between the synthesis of volatiles and the fatty acid and terpene metabolic pathways, and the high expression of the ADH, AAT and TPS genes was key in determining the accumulation of volatiles in pepper fruit. Furthermore, integrative metabolome and transcriptome analysis revealed that 208 differentially expressed genes were highly correlated with 114 volatiles, and the transcription factors of bHLH, MYB, ARF and IAA were identified as fundamental for the regulation of volatile synthesis in pepper fruit. Our results extend the understanding of the synthesis and accumulation of volatiles in pepper fruit.